Daisy and the trouble with coconuts - Gray, Kes; Sharratt, Nick Parsons, Garry (Red Fox London, 2012)
When Daisy goes to the funfair with her grandparents, she is determined to win a coconut. However, winning one is not so easy, as they are just too big and too hairy, and she gets into more trouble. First person recount. Suggested level: junior, primary